The attitude of religious leaders towards violence in Nigeria: case study of mosques and churches - Adua, Sulaiman Sheu (Penerbit Universiti Kebangsaan Malaysia, 2020)
Most of the violence that led to the bloodshed in Nigeria flourished because ofpolitical pungency stage-played through unverified incident wrap-up with faith based encounter. Some of acclaimed religious leader ware turned to political tacticians that focus in helping politician to unleash mayhem in their various community for counter campaign mission which, many of such cases, resulted to carnage that claimed many lives in Nigeria. This manuscript aims to scrutinize the responsibility of a religious leader according to the Scripture (Qur’ān and Bible) in quelling any violence cropped-up within their locality or clash between religious sects.To achieve this aims, survey and comparative method used in selecting relevant verses from both Qur’ān and Bible to expound the divine responsibility on anyone with religious title. This study finds that, politicians corrupted most of religious leaders in Nigeria to have attached political indulgence to the imperatives of their religion. To the extent that, their major responsibility to submerge the view of their people to harmonize their various community had been exchanged with political assignment that breeds unreceptive violence. Since many of this pastors and Imams were most respected in the society, the paper recommends that, to have peace in Nigeria religious leader should be afraid of Almighty God by not accepting a deal from politicians that can lead to bloodshed and killing of innocent life.